Investigating the diurnal cycle of precipitation over Central Africa - P. C. Choumbou; A. J. Komkoua Mbienda; G. M. Guenang; D. Monkam; F. Mkankam Kamga (Meteorological Applications, 2021)
Abstract The present study investigated the reliability of downscaling tool RegCM4.4 to simulate 2002–2006 June–September diurnal cycle precipitation characteristics. Besides their diurnal cycles, the spatial and temporal patterns in precipitation intensity, amount and frequency over Central Africa (CA) are investigated. Diurnal variance, phase and amplitude based on 3‐hourly model simulations are obtained by diurnal harmonics from each 24‐h period. Two statistical measures are used to evaluate model performance: the root mean square error and the index of agreement. The result shows that the RegCM outputs are well simulated compared with reference data in revealing the temporal and spatial patterns of precipitation amount and frequency over the continental area with some systematic wet biases over Cameroon highlands area. Diurnal variability of precipitation frequency and amount are properly well reproduced by the model with an afternoon peak around 1800 LST over entire domain except Atlantic Ocean sub‐region. The model does not properly describe the observed diurnal variation of precipitation intensity over the study area. One of the prominent results is that the pattern of precipitation frequency is quite similar to that of precipitation amount. This strong relationship between these two precipitation characteristics over the entire region of interest suggests that the diurnal precipitation variability is generally determined by how often it rains.